The Role of “Crop Project” on the Development of Blue Economy Tourism in the Eastern Carribean - Marghanita, Clara; Hasyyati Labibah, Imamah; Rahmat , Rhin Khairina (Journal of World Trade Studies, 2023)
Despite its marine diversity and tourism potential, the Caribbean is highly vulnerable to climate change, natural disasters, and damage from human activities. In response, Caribbean governments are actively implementing the Blue Economy framework and the Eastern Caribbean Regional Ocean Policy (ECROP), with support from the World Bank. The World Bank has launched the Caribbean Regional Oceanscape Project (CROP) to drive sustainable development of marine resources in the Eastern Caribbean. This study focuses on assessing CROP's impact on the Eastern Caribbean's Blue Economy, particularly in the tourism sector. The analysis of literature, databases, and agency reports pertaining to the Eastern Caribbean reveals two key findings. First, governments have adopted the Blue Economy as a central strategy to bolster regional fiscal and financial resilience through ECROP policies. Second, despite ECROP's success in increasing economic potential, there are policy imbalances in the various regions due to uneven regulation of the green industry sector. This can be seen in policies in some Eastern Caribbean regions that override the protection of marine ecosystems in favor of achieving state profits in tourism. To encourage the tourism sector as a driver of sustainable development in this region, countries must shift their governance towards more equitable industry regulation, ensure fair access, and prioritize coastal ecological sustainability.